YIELDS IN IRRIGATED AND NON-IRRIGATED SYSTEMS. CASE STUDY BRAILA COUNTY - Elisabeta ROŞU; Ion DONA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The climate changes represent constraining factors for crops growth and development. The progressive warming of the atmosphere, resulting from the synergic action of several natural and anthropic factors, has contributed to the diminution of rainfall at soil level. The irrigation of crops, a technique by which the soil is directly supplied with a supplementary water input, besides the water received naturally, is absolutely necessary in the conditions of arid weather. The present study refers to the influence of the climate changes and the need for irrigations in Braila county, a county with a high agricultural potential, but also to the yields obtained on the main crops in irrigated and non-irrigated systems. In the period 2006-2015, the effective utilization of agricultural areas equipped with irrigation systems was maximum 33%, while in the years 2006 and 2010 respectively, the utilization degree was under 15%. In all the investigated crops, the average yields per hectare obtained under irrigated system were higher than those obtained under non-irrigated system.